2005
DOI: 10.3390/s5040171
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Supramolecular Assembly Film of Porphyrin Bound DNA: Characterization and Catalytic Behaviors Towards Nitric Oxide

Abstract: Chronoamperometric experiments demonstrated a rapid response to the reduction of NO with a linear range from 0.1 to 90 µM and a detection limit of 30 nM at a signal-to-noise ratio of 3. On the other hand, it is the first time to apply high-valent iron porphyrin as catalyst at modified electrode for NO catalytic oxidation at +0.89 vs. Ag|AgCl. The sensor shows a high selectivity of some endogenous electroactive substances in biological systems. The mechanism of response of the sensors to NO is preliminary studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…They are relatively inexpensive and have good stability in solution . Other chemical groups, such as metalloporphyrins have been also tested in NO biosensors; formal potentials in the range of −0.338 to −0.130 V vs. SCE have been reported. A cathodic and an anodic peak were attributed to the Fe(III)/Fe(II) couple of hemin at −0.370±0.012 V and −0.305±0.019 V vs. SCE, respectively, corresponding to the lowest E°′ of −0.338 V vs. SCE at an hemin‐MWCNTs‐chitosan using carbon fiber microelectrodes (CFM) .…”
Section: Direct Electron Transfer Behavior Of Heme Proteins and Porphsupporting
confidence: 62%
See 3 more Smart Citations
“…They are relatively inexpensive and have good stability in solution . Other chemical groups, such as metalloporphyrins have been also tested in NO biosensors; formal potentials in the range of −0.338 to −0.130 V vs. SCE have been reported. A cathodic and an anodic peak were attributed to the Fe(III)/Fe(II) couple of hemin at −0.370±0.012 V and −0.305±0.019 V vs. SCE, respectively, corresponding to the lowest E°′ of −0.338 V vs. SCE at an hemin‐MWCNTs‐chitosan using carbon fiber microelectrodes (CFM) .…”
Section: Direct Electron Transfer Behavior Of Heme Proteins and Porphsupporting
confidence: 62%
“…The iron(III) meso‐tetrakis(N‐methylpyridinium‐4‐yl)porphyrin (Fe(4‐TMPyP) was used to prepare a novel Fe(4‐TMPyP) biosensor with Fe(4‐TMPyP) immobilized with DNA and poly(acrylamide‐co‐diallyldimethylammonium chloride (PADDA), forming a DNA‐bound‐porphyrin complex more stable and biocompatible. The developed complex showed the highest transfer rate (k s =3.12 s −1 ) and consequently the highest E°′ of −0.130 V vs. SCE . The peak potentials of the Fe(III)/Fe(II) couple are in agreement with the other related studies (Table ) supporting the DET of porphyrins .…”
Section: Direct Electron Transfer Behavior Of Heme Proteins and Porphmentioning
confidence: 99%
See 2 more Smart Citations
“…4, upper left panel). Several researchers have demonstrated that the binding of cationic porphyrins to DNA is presumably stabilized by an electrostatic interaction between the positive charges on the porphyrin’s periphery and the negatively charged phosphate group of DNA (36). TMPyP‐DNA binding appears to correspond to the steric electrostatic potential in GC‐rich regions on the DNA (28,37–39).…”
Section: Resultsmentioning
confidence: 99%